Angelomorphic Categories, Early Christology and Discipleship, with Special Reference to Luke-Acts - Fletcher-Louis, Crispin H. T. (1997)
A dissertation arguing that angelic categories are relevant for the formation of early Christian thought, and that Luke is a particularly good example thereof.
Keywords: Christology; Angels; luke-acts; luke; Gospels; New Testament